Evaluation of the extent of interstitial fibrosis in oral squamous cell carcinoma compared with normal oral mucosa and oral epithelial dysplasia. - Fernandez, Alejandra (Journal of Oral Research, 2020)
Objective: To evaluate the extent of interstitial fibrosis in samples of normal oral mucosa (NOM), oral epithelial dysplasia (OED) and oral squamous cell carcinoma (OSCC). Materials and method: Descriptive study. Eighteen samples of NOM, 15 samples of OED, and 13 samples of OSCC were analyzed; all stained with Masson’s trichrome stain. The areas of greatest fibrosis underlying the normal, dysplastic, and malignant neoplastic oral epithelium were identified in order to determine the extent of interstitial fibrosis. Interstitial fibrosis was classified according to its proportion in the total image, being 0 (without fibrosis), +1 (1-25%), 2+ (26-50%), 3+ (51-75%) and +4 (76-100%). Variables were analyzed using the Kruskal-Wallis test and Dunn’s Pairwise posthoc test. Results: The samples of NOM and OED did not present interstitial fibrosis (type 0) in the majority of the cases respectively. OSCC samples were characterized by an extension of type 2+ interstitial fibrosis in 45% of all cases of OSCC. The extent of interstitial fibrosis was different between NOM and OSCC (p<0.001), and between OED and OSCC (p<0.001). Conclusion: The extent of interstitial fibrosis is directly proportional to the malignization of the analyzed samples, being an adequate marker for OSCC.